2018
DOI: 10.3389/fped.2018.00181
|View full text |Cite
|
Sign up to set email alerts
|

Tei Index Is the Best Echocardiographic Parameter for Assessing Right Ventricle Function in Patients With Unrepaired Congenital Heart Diseases With Outflow Tract Obstruction

Abstract: Objective: Magnetic resonance imaging (MRI) and cardiac catheterization are diagnostic tools for right ventricle dysfunction (RVD), but those are expensive and often unavailable techniques. Thus, our objective was to identify clinical and/or echocardiographic variables capable of predicting a catheterization-based diagnosis of RVD.Design: This was cross-sectional, diagnostic test accuracy study, considering the catheterization-based diagnosis of RVD as the gold standard.Patients: Pediatric patients with non-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…11 The measurements used in their study were similar to our approach and demonstrated the following sensitivity and specificity for predicting RV dysfunction: 1) RV fractional area change, 65.9%, 66.7%; and 2) tricuspid annular plane systolic excursion, 70.5%, 78.9%. 11 In 2019, Bao and colleagues evaluated the RV function in 37 children who had undergone surgical repair for TOF, with a mean age of 8 years 6 months. 12 They compared the ejection fraction using cardiac magnetic resonance imaging with ultrasound-measured RV fractional area change, RV annular plane systolic excursion, and speckle-tracking analysis of the RV free wall, and found significant correlations between magnetic resonance-measured ejection fraction and ultrasoundmeasured fractional area change and free wall speckle-tracking strain analysis.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…11 The measurements used in their study were similar to our approach and demonstrated the following sensitivity and specificity for predicting RV dysfunction: 1) RV fractional area change, 65.9%, 66.7%; and 2) tricuspid annular plane systolic excursion, 70.5%, 78.9%. 11 In 2019, Bao and colleagues evaluated the RV function in 37 children who had undergone surgical repair for TOF, with a mean age of 8 years 6 months. 12 They compared the ejection fraction using cardiac magnetic resonance imaging with ultrasound-measured RV fractional area change, RV annular plane systolic excursion, and speckle-tracking analysis of the RV free wall, and found significant correlations between magnetic resonance-measured ejection fraction and ultrasoundmeasured fractional area change and free wall speckle-tracking strain analysis.…”
Section: Discussionmentioning
confidence: 73%
“…Postnatal evaluation of cardiac function in children with TOF has used several techniques described in the current study. In 2018, Marquez‐Gonzalez evaluated RV dysfunction in children with TOF at a mean age 7 years 2 months 11 . The measurements used in their study were similar to our approach and demonstrated the following sensitivity and specificity for predicting RV dysfunction: 1) RV fractional area change, 65.9%, 66.7%; and 2) tricuspid annular plane systolic excursion, 70.5%, 78.9% 11 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The Tei index, first proposed in 1995, evaluates the systolic and diastolic function of the heart. 17 It is the ratio of the sum of the isovolumic systolic interval and the isovolumic diastolic interval to the ejection time of the heart, and thus can directly reflect the overall function of the right ventricle and accurately evaluate right ventricular function. Indeed, studies have shown that among clinical (vascular congestion, functional grade disorder) and echocardiographic (index, right ventricular diameter, area fraction change, tricuspid annular plane systolic shift, S wave, Tei index) variables, Tei index was the only variable with high diagnostic ability.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the Tei index is a noninvasive echocardiographic parameter that can provide valuable information on the overall function of the heart, including in patients with CHD. The Tei index can be used to assess cardiac function, predict outcomes, and guide management in these patients 16 …”
Section: Introductionmentioning
confidence: 99%